2021
DOI: 10.3390/brainsci11020222
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of the First-Time Stroke in the Southwest of Saudi Arabia: A Case-Control Study

Abstract: Worldwide, stroke is the second leading cause of death and a frequent cause of permanent disability. The objective was to identify the first-time stroke modifiable risk factors in the Aseer region, southwest Saudi Arabia. In a multicenter hospital-based case-control study design, all first stroke patients admitted to hospitals in the Aseer region were included consecutively over one year. Age, sex, and geographical residence-matched controls were selected and included in a ratio of 1:1. Data collected included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(43 reference statements)
0
5
0
1
Order By: Relevance
“…Multiple studies around the Kingdom found that hypertension and diabetes are major risk factors for stroke. A study done in Gizan found that 45% of stroke patients had hypertension and 28% had diabetes [ 11 ]. Another study done in the Asser region found that hypertension and diabetes were significantly highly prevalent among stroke Saudi patients at 57.7% and 49.4%, respectively [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple studies around the Kingdom found that hypertension and diabetes are major risk factors for stroke. A study done in Gizan found that 45% of stroke patients had hypertension and 28% had diabetes [ 11 ]. Another study done in the Asser region found that hypertension and diabetes were significantly highly prevalent among stroke Saudi patients at 57.7% and 49.4%, respectively [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus was the second reported risk factor for stroke, present in 71% of the patients. According to WHO, Saudi Arabia is the second-highest country in the Middle East and the seventh globally for diabetes [ 11 ]. A tenfold increase in the prevalence of diabetes was noticed in Saudi Arabia over the past 30 years [ 11 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Berbeda dengan penelitian kasus kontrol di Arab Saudi yang menggunakan batas IMT pengkategorian obesitas adalah >30 kg/m 2 menunjukkan bahwa kondisi obesitas dan kejadian stroke memiliki hubungan yang signifikan dan adjusted odd ratio sebesar 1,95. 29 Menurut teori, terdapat beberapa penjelasan hubungan obesitas dengan kejadian stroke. Pertama, kelebihan berat badan dan obesitas berkaitan dengan peradangan sistemik tingkat rendah yang mengakibatkan peningkatan konsentrasi protein Creaktif.…”
Section: Pembahasanunclassified